Antibiotic Sensitivity Pattern of Pathogenic Bacterial Isolates From Diseased Clarias gariepinus From Selected Ibadan And Ikorodu Farms - Nkechi C. Okere,; A. Olubusola Odeniyi,; K. Olanike Adeyemo, (Journal of Basic & Applied Sciences, 2014)
This study was carried out to isolate, characterise and identify bacteria from diseased Clarias gariepinusand also assess the occurrence of resistance to antimicrobial in isolated bacteria. Samples of diseased African Catfish were collected for a period of six weeks from consenting farms in Ibadan and Ikorodu in Nigeria and examined for clinical signs of disease. Pond water samples along with organs such as gills, skin, intestine, kidney and lungs from these fish were analyzed microbiologically using differential and selective media. Bacteria enumeration, identification and biochemical characterization were carried out and the physiochemical parameters of the water samples determined. All isolates were subjected to antibiotic sensitivity test using the standard Kirby-Bauer disc diffusion method. The total bacterial load for the organs ranged between 3.0 x 104 (lungs sample) and 6.0 x 107cfu/g (gill sample). The gills had the highest average total bacterial count, while lungs had the least. Morphologically unique bacterial isolates obtained included Salmonella (14 isolates), Pseudomonas (4 isolates), Aeromonas (2 isolates), Edwardsiella (3 isolates) and Shigella (3 isolates). These isolates displayed antibiotic resistance profile to the following: Ceftazidime (38%), Cefuroxime (77%), Gentamicin (37%), Cefixime (73%), Ofloxacin (23%), Augmentin (66%), Nitrofurantoin (58%) and Ciprofloxacin (15%). Two Salmonella isolates had multi-drug resistance pattern. This study showed that indiscriminate use of unlicensed or unapproved antibiotics for aquaculture portends significant hazards to public health therefore disease prevention is preferable through good culture and health management to ensure optimum yields and wholesome products.